Unusual staphylococcal toxic shock syndrome presenting as a scarlet-like fever. (November 2015) - Andrey, D.O.; Ferry, T.; Siegenthaler, N.; Fletcher, C.; Calmy, A.; Lina, G.; Emonet, S.
Abstract: Diagnosis of nonmenstrual staphylococcal toxic shock syndrome (TSS) is often challenging. A female medical colleague had a rare entity, a staphylococcal pharyngitis complicated by TSS. The diagnosis was confirmed by isolation of tst -positive Staphylococcus aureus in throat culture and by identification of a specific Vβ2 expansion pattern of her T lymphocytes. Recent improvements in microbiology can be of great help for the diagnosis of nonmenstrual TSS.